Investigating the Links between Environmental Performance, Innovation and Firm Performance in the UK industrial sector - AFSHAR, SAMAN (2011)
This paper attempts to study the links among environmental performance, innovation and firm performance by using primary data which has been obtained from the Environmental Protection Survey for period of 2000-2008. Both T-test and regression analyses (i.e. Moderated and mediated regression analysis) have been used in this study to examine direct effect of environmental performance on firm performance and investigating the indirect impact of environmental performance on firm performance through innovation. In addition this paper examined the characteristics of firms in the UK who adopted ISO14001 in their organization. Furthermore it explores the impacts of different environmental management approaches on firm performance and finally it studies the impact of flexible regulations on firm performance. After testing 16 hypotheses, this study found that: (1) environmental performance measured in terms of environmental protection expenditure positively influences firm performance, which supports win-win hypothesis. (2) TINTE and EOPE expenditure negatively influence firm performance in the short run. (3) TEPE in the media of solid waste positively influences firm performance, whilst in media of water pollution this influence is negative. (4) TINT in the media of solid waste has no significant impact on firm performance, whilst in media of water integrated expenditures it positively influences firm performance.(5) Innovation has a positive, moderating effect on the relationship between TEPE,INTE and firm performance, whilst this moderating effect is negative on the relationship between EOP and firm performance.(6) Innovation is found to have a negative moderating effect in the case of TEPE in water pollutions, whilst this effect is positive in media of solid. (7) This study found that there is no significant difference between EPE across the ISO firms and non-ISO firms, likewise no significant difference have found between numbers of employees across two groups. In contrast firm size differs significantly across two groups. This study has implications for future empirical research, firm management and policy makers. For future study considering other countries would lead us to gain more general results to see whether other countries have same experience regarding the relationship between environmental performance and firm performance or not. For firm managements our results suggest that firms should include the environmental initiatives as part of their long term strategic plans in order to see the positive impact of that on the firm performance. Finally for policymakers our results imply that flexible regulations provide the opportunity for firms to reach environmental standards by adopting new methods or technologies and not just by implementing the best available technologies.